2021
DOI: 10.1007/s10896-021-00279-0
|View full text |Cite
|
Sign up to set email alerts
|

Advocate and Survivor Perspectives on the Role of Technology in Help Seeking and Services with Emerging Adults in Higher Education

Abstract: Emerging adults, aged 18-25, have come of age in a technology oriented world. The internet has been critical in mediating their personal relationships and their understanding of daily life. Emerging adults are also at unique risk of experiencing intimate partner and sexual violence (IPV & SV) Given the increasing infusion of information communication technology (ICT) into anti-violence advocacy, and the broad use of ICT among college-attending emerging adults, this study aimed to explore how both survivors and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 69 publications
0
11
0
Order By: Relevance
“…Online platforms and communities on GSN apps may provide initial support to those individuals. A recent qualitative study also suggested that the use of mobile and web-based apps has the benefit of supporting survivors of violence and preventing future violence (Voth Schrag et al, 2022 ). Given the high prevalence of IPV victimization among SMM, programs aiming to promote formal and informal help-seeking behaviors among IPV victimization survivors should consider adapting and integrating programs into GSN apps.…”
Section: Discussionmentioning
confidence: 99%
“…Online platforms and communities on GSN apps may provide initial support to those individuals. A recent qualitative study also suggested that the use of mobile and web-based apps has the benefit of supporting survivors of violence and preventing future violence (Voth Schrag et al, 2022 ). Given the high prevalence of IPV victimization among SMM, programs aiming to promote formal and informal help-seeking behaviors among IPV victimization survivors should consider adapting and integrating programs into GSN apps.…”
Section: Discussionmentioning
confidence: 99%
“…In the years prior to the pandemic, virtual services were already gaining attention as an additional tool for victim service providers, as the proliferation of internet and smartphone use changed the way people communicate and build relationships (Merolli et al, 2014;Voth Schrag et al, 2021). With the service sector's focus on providing individualized services built around the preferences and needs of each survivor, agencies had begun to build virtual services, such as chat and text-based crisis hotlines, to allow individuals to engage with services using modes of communication most comfortable for them (Nesmith, 2018;Wood, Hairston, et al, 2021b).…”
Section: Virtual Servicesmentioning
confidence: 99%
“…Emerging evidence highlights the role of information communication technology in bridging this gap, particularly as a quick "how is it going?" text-based check in seemed like a viable route for this communication for many participants in this study (Voth Schrag et al, 2021). Ongoing work should explore the potential for virtual services, along with mobile advocacy (Sullivan & Olsen, 2016) to be paired with rapid rehousing models to maximize services efficacy.…”
Section: Discussionmentioning
confidence: 97%
“…Interviews indicated that survivors sometimes found accessing advocate support challenging, as they were not colocated in the same physical space as might be the case in an emergency shelter or onsite transitional housing program. Emerging evidence highlights the role of information communication technology in bridging this gap, particularly as a quick “how is it going?” text-based check in seemed like a viable route for this communication for many participants in this study (Voth Schrag et al, 2021). Ongoing work should explore the potential for virtual services, along with mobile advocacy (Sullivan & Olsen, 2016) to be paired with rapid rehousing models to maximize services efficacy.…”
Section: Discussionmentioning
confidence: 99%